Teachers’ Views on the Moral, Social, and Emotional Dimensions of Distance Learning - Mlinar, Karmen; Peček, Mojca (Revija za elementarno izobraževanje, 2023)
This paper focuses on the moral, social, and emotional dimensions of distance learning during COVID-19, as these dimensions have been neglected in most studies. The results of our study show that most primary school teachers (n=71) mostly pursued these dimensions unsystematically or not at all. They focused mainly on pupils’ interpersonal relationships and discipline, less on their motivation and well-being. Most teachers expressed a negative opinion about the possibility for addressing these dimensions, many understanding this as the parents’ duty. Therefore, if distance learning is reintroduced, it would be important to think about the possibilities and to create guidelines that include these dimensions.
Keywords: distance learning, primary school teachers, COVID-19, primary education